Validated high performance liquid chromatographic method for analysis of fenvalerate pesticide in chilies by quechers extraction cleanup and high liquid chromatography - Altorshani, A.A.; Bakar, N.K.A.; Eid, E.E.M. (2010)
Problem statement: Contamination associated with pesticide use has increased as well, adversely impacting the environment and causing human health risks through residues on food. Approach: This study reports the extraction of Fenvalerate (FE) in chilies using QuEChERS based on High Performance Liquid Chromatography (HPLC) describes a simple, fast and inexpensive method. The chillie was extracted with acetonitrile Aliquots were cleaned-up using Solid Phase Etraction (dSPE), a primary-secondary amine carbon black. Reversed-phased HPlc system with PDA detection was used for the separation identification and quantification of all these analyses using acetonitrile methanol-potassium dehydrogenate phosphate (50:40:10) as mobile phase. Results: Limit of detection of 0.01 Î¼g mL was obtained. Calibration curves that constructed for the analyzes spiked into samples followed linear relationships with good correlation coefficients (R2>0.9944). In this method was found to be precise, specific and accurate for detection and analysis of Fenvalerate in chilies. Conclusion: QuEChERS methods are convenient, rugged methods that simplify extract cleanup, reduce material costs and improve sample throughout. Here we demonstrate the effectiveness of QuEChERS sample cleanup using a multiresidue analysis of pesticide on chilies.